PHYSICAL ACTIVITY OF A FUTURE TEACHER IN HEALTH INSTITUTIONS IN THE LIGHT OF PERSONALITY-ORIENTED PEDAGOGY - Карасєвич, Сергей (SWorldJournal, 2022)
The ways of organizing a healthy lifestyle in a summer health facility have been identified and substantiated. The role of the future teacher in the summer health institution in the process of physical activity in the light of personality-oriented approac